Ghrelin Enhancer, the Latest Evidence of Rikkunshito - Yamada, Chihiro; Hattori, Tomohisa; Ohnishi, Shunsuke; Takeda, Hiroshi (Frontiers in Nutrition, 2021)
Rikkunshito is a Japanese herbal medicine (Kampo) that has been attracting attention and researched by many researchers not only in Japan but also worldwide. There are 146 rikkunshito articles that can be searched on PubMed by August 2021. The reason why rikkunshito has attracted so much attention is due to an epoch-making report (Gastroenterology, 2008) discovered that rikkunshito promotes the secretion of the orexigenic peptide ghrelin. Since then, many researchers have discovered that rikkunshito has a direct effect on the ghrelin receptor, GHS-R1a, and an effect of enhancing the ghrelin signal to the brain. Additionally, a lot of evidence that rikkunshito is expected to be effective for various gastrointestinal diseases have also been demonstrated. Numerous basic and clinical studies have suggested that rikkunshito affects (ⅰ) various discomforts caused by anticancer drugs, gastroesophageal reflux disease, functional dyspepsia, (ⅱ) various stress-induced anorexia, (ⅲ) hypophagia in the elderly, and (ⅳ) healthy lifespan. In this review, as one who discovered the ghrelin enhancer effect of rikkunshito, we will review the research of rikkunshito so far and report on the latest research results. Finally, it also describes ninjinyoeito, as possibility of other Kampo medicine similar to rikkunshito.